Respuesta :
Answer : A) Â [tex] f(x) = (x-1)^2 - 7 [/tex]
Standard form of equation is [tex] f(x) = x^2 - 2x - 6 [/tex]
The vertex form of equation is [tex] y= (x-h)^2 + k [/tex]
where (h,k) is the vertex
To find x coordinate of vertex we use formula [tex] h =\frac{-b}{2a}[/tex]
[tex] f(x) = x^2 - 2x - 6 [/tex], a=1, b=-2 and c=-6
Plug in the values
[tex] h =\frac{-b}{2a}=\frac{-(-2)}{2*1}= 1 [/tex]
Now plug in x=1 in the equation
[tex] k =f(x) = 1^2 - 2(1) - 6 = 1-2-6= -7 [/tex]
h= 1 Â and k=-7
The vertex form of equation is [tex] y= (x-h)^2 + k [/tex]
Plug in the values h=1 and k=-7
[tex] f(x)= (x-1)^2 - 7 [/tex]